Global China as Method - Franceschini, Ivan (Social Sciences, 2022)
After four decades of integration into the global socioeconomic system, discussions of China continue to be framed by a core assumption: that the country represents a fundamentally different and separate 'other'. This Element seeks to illuminate the ways in which China and it's people form an integral part of the global capitalist system.